2015
DOI: 10.1038/ncomms9809
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced spontaneous free-carrier generation in semiconducting single-walled carbon nanotubes

Abstract: Strong quantum confinement and low dielectric screening impart single-walled carbon nanotubes with exciton-binding energies substantially exceeding kBT at room temperature. Despite these large binding energies, reported photoluminescence quantum yields are typically low and some studies suggest that photoexcitation of carbon nanotube excitonic transitions can produce free charge carriers. Here we report the direct measurement of long-lived free-carrier generation in chirality-pure, single-walled carbon nanotub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 50 publications
6
58
0
Order By: Relevance
“…The impact of TOA‐perovskite growth on charge transport in perovskites was studied by comparing the photoconductance (Δ G ) of TOA‐ and SE‐perovskite films using fp‐TRMC. This technique has shown its versatility in characterizing charge‐carrier mobilities, charge‐carrier generation efficiency, and subsequent carrier‐recombination dynamics in various organic/inorganic material systems . In fp‐TRMC, Δ G ( t ) is related to the product (Φ( t )Σ µ ) of carrier‐generation yield (Φ( t )) and both electron ( µ e ) and hole ( µ h ) mobilities (Σ µ = µ e + µ h ).…”
Section: Charge‐carrier Mobility Lifetime and Trap Density Of Toa‐ mentioning
confidence: 99%
“…The impact of TOA‐perovskite growth on charge transport in perovskites was studied by comparing the photoconductance (Δ G ) of TOA‐ and SE‐perovskite films using fp‐TRMC. This technique has shown its versatility in characterizing charge‐carrier mobilities, charge‐carrier generation efficiency, and subsequent carrier‐recombination dynamics in various organic/inorganic material systems . In fp‐TRMC, Δ G ( t ) is related to the product (Φ( t )Σ µ ) of carrier‐generation yield (Φ( t )) and both electron ( µ e ) and hole ( µ h ) mobilities (Σ µ = µ e + µ h ).…”
Section: Charge‐carrier Mobility Lifetime and Trap Density Of Toa‐ mentioning
confidence: 99%
“…This can be visualized with a so-called action spectrum, in which the wavelength-dependent Σμ is directly compared to the FA spectrum. 22,23 Figures 2b and 2d (dashed lines) show the action spectra for the CH3NH3PbI3 thin film at 300 K (b) and at 120 K (d), together with the temperature-dependent FA spectra (solid lines).…”
mentioning
confidence: 99%
“…This prediction is considered as one of the possible sources of free carriers in recent photocurrent measurements, along with phonon mediated E 22 free carrier disassociation pathways [10]. Recent studies at very low excitation densities have indeed confirmed that single exciton disassociation pathways exist to generate free carriers [11]. However, it has yet to be shown whether the very efficient exciton-exciton annihilation (EEA) process in SWCNTs acts as an additional source of free carriers, as has been theorized.…”
Section: Introductionmentioning
confidence: 90%
“…The fluence dependence of the optical absorption and PL are measured under ultrafast (∼150 fs) E 22 resonant optical excitation. While this technique is not sensitive to linear sources of free-carriers, such as E 22 and E 11 disassociation [11], it is highly sensitive to nonlinear sources of free-carriers, namely density dependent Auger ionization. We show that, despite strong PL saturation and excitation fluences far exceeding the BGR theshhold calculated by Konabe and Okada [9], the optical absorption remains constant, indicating the Auger process does not lead to exciton disassociation.…”
Section: Introductionmentioning
confidence: 99%